2014
DOI: 10.1097/shk.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Cardiomyocyte Peroxisome Proliferator-Activated Receptor γ Enhances Myocardial Ischemia-Reperfusion Injury in Mice

Abstract: The nuclear transcription factor peroxisome proliferator-activated receptor-γ (PPARγ) is a key regulator of the inflammatory response to an array of biologic insults. We have previously demonstrated that PPARγ ligands reduce myocardial ischemia-reperfusion injury in rodents. In the current study, we directly determined the role of cardiomyocyte PPARγ in ischemia-reperfusion injury, employing a model of conditional cardiomyocyte-specific deletion of PPARγ in vivo. In mice, α-myosin heavy chain-restricted Cre-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The new complex can bind to NF-κB-specific promoter sequences and induce the expression of other inflammatory factors (eg, tumor necrosis factor α, interleukin-1 [IL-1], interleukin-6 [IL-6], intercellular adhesion molecule-1 [ICAM-1], and vascular cell adhesion molecule-1 [VCAM-1]), which can promote inflammatory responses. 58,75,76…”
Section: An Overview Of Pparγmentioning
confidence: 99%
“…The new complex can bind to NF-κB-specific promoter sequences and induce the expression of other inflammatory factors (eg, tumor necrosis factor α, interleukin-1 [IL-1], interleukin-6 [IL-6], intercellular adhesion molecule-1 [ICAM-1], and vascular cell adhesion molecule-1 [VCAM-1]), which can promote inflammatory responses. 58,75,76…”
Section: An Overview Of Pparγmentioning
confidence: 99%
“…Therefore, chronic deactivation of the PPAR- α signaling pathway may upset the normal equilibrium between oxidant production and antioxidant defenses, which can contribute to cardiac damage [ 58 ]. A recent study in PPAR- γ KO mice revealed that PPAR- γ plays a crucial protective role in cardiomyocytes and may prevent myocardial ischemia-reperfusion injury by modulating NF- κ B-associated inflammatory mechanisms in the infarcted myocardium [ 76 ].…”
Section: Ppar Functions In the Cardiovascular Systemmentioning
confidence: 99%
“…PPARg, as a potent regulator of FA metabolism and inhibitor of inflammation, plays an important protective role in the heart muscle during ischemia/reperfusion, and TZDs had beneficial effects in animal models. On the other hand, conditional deletion of PPARg in cardiomyocytes significantly augmented the myocardial damage through inflammation [110].…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%